The effect of subspinal Le Fort 1 corticotomy on nasal morphology in surgically assisted rapid palatal expansion. Issue 4 (April 2022) - Michaux, D.; Van de Casteele, E.; Dielen, D.; Van Hemelen, G.; Nadjmi, N.
Abstract: The purpose of this retrospective study was to evaluate the influence of subspinal Le Fort 1 corticotomy (SLF1C) on nasal morphology in patients treated with surgically assisted rapid palatal expansion (SARPE) using three-dimensional (3D) stereophotogrammetry images. A total of 64 patients were enrolled in the study and divided into two groups according to the surgical approach that was used: in group 1 ( n = 32) SARPE was performed using a conventional Le Fort 1 corticotomy (CLF1C), and in group 2 ( n = 32) SARPE was performed using a subspinal Le Fort 1 corticotomy (SLF1C). Measurements of alar and columellar width, and nasolabial angle were taken on 3D stereophotogrammetry images before and after SARPE using Vectra 3D camera system. Both surgical groups showed a statistically significant increase in alar and columellar width, and nasolabial angle postoperatively (p<0.05). SLF1C resulted in significantly smaller changes of the columellar base postoperatively (p=0.0456). The data suggests that SARPE with an osteotomy of the anterior nasal spine as an additional step to the conventional Le Fort 1 corticotomy results in a smaller increase of the columellar base.